Perencanaan Naskah Naratif Video Dokumenter “Bisakah Aku Kembali?” tentang Rehabilitasi Kukang Jawa - Anggita Nuringtyas; Siti Arifa Rosa; Encang Saepudin; FX. Ari Agung Prastowo (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
A scriptwriter is the individual responsible for organizing and designing the storyline as the foundation for the documentary video production process. In the production of the documentary video “Bisakah Aku Kembali?”, the scriptwriter plays a crucial role in processing facts and research data into a structured narrative, thereby delivering messages informatively while building emotional resonance with the audience. The purpose of this report is to explain the narrative script planning process and describe the application of the three-act structure as the primary approach in building the storyline. The writing method used is descriptive through the stages of research, observation, and interviews, processing field facts into a structured narrative. Synthesis of the work was carried out by applying the three-act structure, consisting of Act I (setup) to introduce the issue and context of rehabilitation, Act II (confrontation) to develop conflict through medical realities and animal behavior during rehabilitation, and Act III (resolution) to present the conclusion and reflection on the relationship between humans and nature. In conclusion, documentary script planning using a narrative approach and a three-act structure is capable of producing a coherent, informative, and reflective storyline in conveying conservation messages regarding the rehabilitation of the Javan Slow Loris as a protected species.